School Environmental Exploration Learning in Improving Science and Mathematics Abilities in Early Childhood in DA Cokroaminoto 02 Gemuruh Kindergarten, Banjarnegara District - Salsa Billa, Aidda; Formen, Ali (BELIA Early Childhood Education Papers, 2024)
Based on research conducted at TK DA Cokroaminoto 02 Gemuruh, Banjarnegara Regency, science and mathematics learning still uses learning media that tend to focus on magazines or books. Therefore, this study aims to determine the increase in science and mathematics skills in early childhood. This study uses a quantitative method with Pre-Experiment. This study uses a One Group Pretest-Posttest Design. Data analysis techniques used normality tests, average increase tests (N-Gain) and average difference tests (t-test). The data analysis techniques used are descriptive analysis, hypothesis testing through the Paired Sample t-Test and the N-Gain Test. All calculations were performed using SPSS IMB 26. The science and mathematics ability before being given treatment was 51.75 then after being given treatment of school environmental exploration learning increased to 95.50. The amount of increase before and after being given treatment was 43.75. Based on statistical calculations through the Paired Sample t-Test, it shows that the calculated t must be smaller than the t table (t calculated < t table) and sig <0.05. The results show that the calculated t <t table is -22.682 <2.093 and sig 0.000 < 0.05 so that Ha is accepted. Based on the results of the N-Gain test, it was obtained as much as 0.9073 which means there is an average increase in the pretest and posttest scores with a high category. The conclusion in this study is that environmental exploration learning is effective in improving science and mathematics abilities in early childhood.